Interlaminar shear strength study on CFRP/Al hybrid laminates with different properties - Costanzo Bellini; Vittorio Di Cocco; Luca Sorrentino (Fracture and Structural Integrity)
FML (Fibre Metal Laminate) is a hybrid material that presents outstanding structural properties, such as resistance to cyclic and dynamic loads, together with low specific weight. This material consists of metal sheets alternating to composite material layers. In the present work, the ILSS (Interlaminar Shear Strength) was evaluated for different types of carbon fibre/aluminium FML, produced varying the layer thickness and the bonding solution of layers. In fact, FMLs consisting of one or two metal sheets (a parameter strictly connected to the layer thickness, as the metal/composite volume fraction was kept at constant value) and bonded with structural adhesive or prepreg resin were considered for this study. The ILSS was determined according to the three-point bending method with short beam specimens. The experimental tests evidenced an effect of the adhesion methodology on the ILSS value, while the layer thickness did not influence the interlaminar strength. The mechanical behaviour after the maximum load point was investigated too, evaluating the trend of the shear stress as a function of the loading nose displacement.